Perilaku Kehidupan Ibu Rumah Tangga Dalam Menjalankan Peran Sosial Untuk Pendidikan Anak - Nurhayati Takahegesang; Rauf A. Hatu; Sainudin Latare; Sabrina Nadia (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Children’s education is an important factor in the development of human resource quality and the success of community development. Within the family environment, housewives play a strategic role as the first educators who contribute to shaping children’s character, learning habits, and educational motivation. However, in Modelomo Village, Kabila Bone Subdistrict, Bone Bolango Regency, differences in the behavior of housewives in carrying out their social roles for children’s education are still found, as shown by the level of assistance, supervision, and attention to children’s learning activities. This study aims to understand and examine the daily behavior of housewives in carrying out their social roles in children’s education in Modelomo Village, Kabila Bone Subdistrict, Bone Bolango Regency. The research uses a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation. Research informants were selected purposively, namely housewives who have school-aged children and are directly involved in their children’s educational process. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that housewives perform social roles as educators, caregivers, motivators, and supervisors in children’s education. These roles are realized through learning assistance, providing motivation, supervising gadget use, communicating with schools, and participating in social activities that support children’s education. The social role of mothers has a positive impact on children’s discipline, learning motivation, responsibility, and enthusiasm for attending school. The conclusion of this study indicates that the behavior of housewives has a significant influence on children’s educational success. The more optimal the social role performed by mothers, the greater the opportunity for children to develop both academically and socially.